Junín virus infection impairs stress-granule formation in Vero cells treated with arsenite via inhibition of eiF2α phosphorylation - Linero, F.N. (2011)
Stress granules (SGs) are ephemeral cytoplasmic aggregates containing stalled translation preinitiation complexes involved in mRNA storage and triage during the cellular stress response. SG formation is triggered by the phosphorylation of the alpha subunit of eIF2 (eIF2α), which provokes a dramatic blockage of protein translation. Our results demonstrate that acute infection of Vero cells with the arenavirus Junidotless ́n (JUNV), aetiological agent of Argentine haemorrhagic fever, does not induce the formation of SGs. Moreover, JUNV negatively modulates SG formation in infected cells stressed with arsenite, and this inhibition correlates with low levels of eIF2α phosphorylation. Transient expression of JUNV nucleoprotein (N) or the glycoprotein precursor (GPC), but not of the matrix protein (Z), inhibits SG formation in a similar manner, comparable to infectious virus. Expression of N and GPC also impaired eIF2α phosphorylation triggered by arsenite. A moderate inhibition of SG formation was also observed when DTT and thapsigargin were employed as stress inducers. In contrast, no inhibition was observed when infected cells were treated with hippuristanol, a translational inhibitor and inducer of SGs that bypasses the requirement for eIF2α phosphorylation. Finally, we analysed SG formation in persistently JUNV-infected cells, where N and GPC are virtually absent and truncated N products are expressed abundantly.Wefound that persistently infected cells show a quite normal response to arsenite, with SG formation comparable to that of uninfected cells. This suggests that the presence of GPC and/or N is crucial to control the stress response upon JUNV infection of Vero cells © 2011 SGM.